(untitled) (Trabalho & Educação, 2018)
The objective of the study is to analyze how the scientific community has evaluated the effectiveness of the professional training offered in the modality of distance education. To achieve this goal, an integrative literature review was conducted according to a methodology that could be replicated by other researchers. Five stages were considered in the literature review process: identification of the theme and the research question; selection of a bibliographic portfolio; elaboration of categories of analysis; analysis and interpretation of results; and presentation of knowledge synthesis. The results indicated that there was no consensus in the literature about the definition of effectiveness of professional training, generally evaluated by gaining knowledge after the course, by observing the results in professional practice or by applying satisfaction questionnaires. The most used evaluation model was Kirkpatrick, which shows the levels of reaction, learning, behavior and results. The study demonstrated evidence that the effectiveness of professional training offered in the context of the distance education is related to the development of skills, attitudes and motivation. In addition, personal characteristics, pedagogical and institutional mediation may influence the development of these latent traits. ___ O objetivo do estudo é analisar como a comunidade científica tem avaliado a efetividade da formação profissional ofertada na modalidade de educação a distância. Para alcançar esse objetivo, foi realizada uma revisão integrativa de literatura, conduzida de acordo com uma metodologia possível de ser reproduzida por outros pesquisadores. Cinco etapas foram contempladas no processo de revisão de literatura: identificação do tema e da questão de pesquisa; seleção de um portfólio bibliográfico; elaboração de categorias de análise; análise e interpretação dos resultados; e apresentação da revisão/síntese do conhecimento. Os resultados indicaram não haver consenso na literatura acerca da definição de efetividade da formação profissional, avaliada, em geral, pelo ganho de conhecimento após o curso, pela observação dos resultados na prática profissional ou com a aplicação de questionários de satisfação. O modelo de avaliação mais utilizado foi o de Kirkpatrick, o qual apresenta os níveis da reação, aprendizagem, comportamento e resultados. O estudo demonstrou evidências de que a efetividade da formação profissional ofertada no contexto da modalidade EaD está relacionada ao desenvolvimento de habilidades, atitudes e motivação. Além disso, características pessoais, da mediação pedagógica e institucionais podem influenciar o desenvolvimento desses traços latentes.